What makes a plant science manuscript successful for publication? - Setter, Timothy; Munns, Rana; Stefanova, Katia; Shabala, Sergey (CSIRO, 2020)
Dissemination of new knowledge is arguably the most critical component of the academic activity. In this context, scientific publishing is a pinnacle of any research work. Although the scientific content has always been the primary measure of a paper’s impact, by itself it may not always be sufficient for maximum impact. Good scientific writing and ability to meet priority characteristics of the target journal are essential, and inability to meet appropriate standards may jeopardise the chances for dissemination of results. This paper analyses the key features necessary for successfully publishing scientific research manuscripts. Conclusions are validated by a survey of 22 international scientific journals in agriculture and plant biology whose editors-in-chief have provided current data on key features related to manuscript acceptance or rejection. The top priorities for manuscript rejection by scientific journals in agriculture and plant biology are: (1) lack of sufficient novelty; (2) flaws in methods or data interpretation; (3) inadequate data analyses; and (4) poor critical scientific thinking. The inability to meet these requirements may result in rejection of even the best set of data. Recommendations are made for critical thinking and integration of good scientific writing with quality research. These recommendations will improve the quality of manuscripts submitted for publication to scientific journals and hence improve their likelihood of acceptance.